Disrupted gut microbiota aggravates working memory dysfunction induced by high-altitude exposure in mice - Zhao, Zhifang; Cui, Dejun; Wu, Guosong; Ren, Hong; Zhu, Ximei; Xie, Wenting; Zhang, Yuming; Yang, Liu; Peng, Weiqi; Lai, Chunxiao; Huang, Yongmei; Li, Hao (Frontiers in Microbiology, 2022)
The hypothesis of microbiome-gut-brain axis which has been widely accepted by a number of previous reported may be essential to explain the impact of high altitude exposure on human body, especially the brain function. However, related studies are still limited and the underlying mechanism remains unclear. Therefore, this study aimed to find out whether or not high altitude induced working memory dysfunction could be exacerbated when the gut microbiota is disturbed, which may provide more evidence for the the link between microbiome-gut-brain axis and high altitude exposure. C57BL/6 mice were randomly divided into three groups, the Control group, high altitude exposed (HAE) group, and high-altitude exposed with antibiotics treatment (HAE-A) group. The the HAE and HAE-A groups were exposed to a low-pressure oxygen chamber simulating an altitude of 3500-4000m for 14 days with the air pressure in the chamber set to 60-65 kPa, and air pressure level for Control group was maintained at 94.5 kPa instead. Antibiotic water (mixed with 0.2g/L of ciprofloxacin and 1g/L of metronidazole) was provided to the HAE-A group. Based on the results of novel object test and P300 of the oddball behavioral paradigm training test, the working memory dysfunction was aggravated by antibiotic treatment. We determined the antioxidant capacity in the prefrontal cortex, and find the significantly negative influences (P < 0.05) of disturbed gut microbiota on total antioxidation capacity (T-AOC) and malondialdehyde (MDA) content as well as the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). The same trend was also observed in the results of apoptosis-related functional protein contents and mRNA expression levels in the prefrontal cortex, especially the levels of bcl-2, Bax and caspase-3. The high altitude environment and antibiotic treatment greatly affected the richness and diversity of colonic microbiota, and reorganized the composition and structure of the microbial community. S24-7, Lachnospiraceae and Lactobacillaceae could be the three microbial taxa with the most obvious changes under the stimulation of external factors in this study. In addition, the correlation analysis between colonic microbiota and cognitive function of mice found that Helicobacteraceae might to be closely related to behavioral results.